Development of a droplet digital PCR assay for the detection of BK polyomavirus - Lu Ai; Yating Zhao; Chianru Tan; Lu Bai; Gang Huang; Ruizhi Wang; Hao Huang; Xuegao Yu; Yong Guo; Peisong Chen (Microbiology Spectrum)
ABSTRACT The objective of this study was to establish a more sensitive and specific diagnostic method for detecting plasma BK polyomavirus (BKPyV) DNA load in patients after renal transplantation using droplet digital polymerase chain reaction (ddPCR) and to validate the methodology. The linear range, lower limit of detection, accuracy, precision, and specificity of the detection system were evaluated by using the WHO BKPyV standard (7.2 log10 IU/mL) as a reference, in accordance with the relevant documents of the Clinical and Laboratory Standards Institute. Plasma samples were collected from 74 renal transplantation patients with urinary BKPyV-DNA levels exceeding 7 log10 copies/mL. Quantitative PCR (qPCR) and ddPCR were performed, and their diagnostic efficacy for BKPyV-DNA in the diagnosis of BK polyomavirus-associated nephropathy was evaluated using a receiver operating characteristic (ROC) curve. The coefficients of variation for the repeated detection of BKPyV standard DNA were 2.55 and 4.71 at concentrations of 6.2 and 3.2 log10 IU/mL, respectively. The linear range was 2.2–6.2 log10 IU/mL, and the lowest detection limit was 100 IU/mL. By utilizing histopathological examination of renal biopsy as the gold standard for BKPyV diagnosis, the area under the ROC curve of 74 post-transplantation plasma samples detected by the ddPCR system was found to be 0.875 (95% CI: 0.797–0.953, P < 0.01). The optimal threshold was 512.86 copies/mL, with a sensitivity of 90.0% and a specificity of 67.6%. In comparison, the area under the ROC curve for qPCR was 0.668 (95% CI: 0.583–0.752, P < 0.01), with an optimal threshold of 11,481.54 copies/mL, a sensitivity of 35.0%, and a specificity of 100.0%. Pairwise comparison (Delong test) of the ROC curves of the two systems showed a significant difference in the area under the curve, with a difference of 0.207 and a P-value <0.01. The BKPyV nucleic acid detection system, based on ddPCR, is appropriate for the regular monitoring of the BK polyomavirus, specifically in plasma samples containing low viral DNA loads while it provides the benefits of both absolute quantification and high sensitivity.IMPORTANCEIt was previously believed that droplet digital polymerase chain reaction had limitations, including high cost, limited throughput, and cumbersome operation, which hindered its widespread application in clinical practice. However, the current fully automated digital PCR platform, combined with streamlined operations, can detect 96 samples at once, and the entire process can be completed within an hour, laying a solid foundation for its extensive use.